Evaluating anti-viral effect of Tylvalosin tartrate on porcine reproductive and respiratory syndrome virus and analyzing the related gene regulation by transcriptomics - Xingzhen Tang; Cong Wang; Weifeng Sun; Weixin Wu; Shaohui Sun; Jin Wan; Guangshan Zhu; Nini Ma; Xiaoping Ma; Ruihua Xu; Qiushi Yang; Yindi Dai; et al. (Virology Journal, 2023)
Abstract Background Porcine reproductive and respiratory syndrome virus (PRRSV) is an economically important pathogen, characterized by its genetic and antigenic variation. The PRRSV vaccine is widely used, however, the unsatisfied heterologic protection and the risk of reverse virulence raise the requirement to find some new anti-PRRSV strategies for disease control. Tylvalosin tartrate is used to inhibit PRRSV in the field non-specifically, however, the mechanism is still less known. Methods The antiviral effects of Tylvalosin tartrates from three producers were evaluated in a cell inoculation model. Their safety and efficacy concentrations, and effecting stage during PRRSV infection were analyzed. And, the Tylvalosin tartrates regulated genes and pathways which are potentially related to the anti-viral effect were further explored by using transcriptomics analysis. Last, the transcription level of six anti-virus-related DEGs was selected to confirm by qPCR, and the expression level of HMOX1, a reported anti-PRRSV gene, was proved by western blot. Results The safety concentrations of Tylvalosin tartrates from three different producers were 40 µg/mL (Tyl A, Tyl B, and Tyl C) in MARC-145 cells and 20 µg/mL (Tyl A) or 40 µg/mL (Tyl B and Tyl C) in primary pulmonary alveolar macrophages (PAMs) respectively. Tylvalosin tartrate can inhibit PRRSV proliferation in a dose-dependent manner, causing more than 90% proliferation reduction at 40 µg/mL. But it shows no virucidal effect, and only achieves the antiviral effect via long-term action on the cells during the PRRSV proliferation. Furthermore, GO terms and KEGG pathway analysis was carried out based on the RNA sequencing and transcriptomic data. It was found that the Tylvalosin tartrates can regulate the signal transduction, proteolysis, and oxidation-reduction process, as well as some pathways such as protein digestion and absorption, PI3K-Akt signaling, FoxO signaling, and Ferroptosis pathways, which might relate to PRRSV proliferation or host innate immune response, but further studies still need to confirm it. Among them, six antivirus-related genes HMOX1, ATF3, FTH1, FTL, NR4A1, and CDKN1A were identified to be regulated by Tylvalosin tartrate, and the increased expression level of HMOX1 was further confirmed by western blot. Conclusions Tylvalosin tartrate can inhibit PRRSV proliferation in vitro in a dose-dependent manner. The identified DEGs and pathways in transcriptomic data will provide valuable clues for further exploring the host cell restriction factors or anti-PRRSV target.